alibaba nguyễn
22 tháng 1 2017 lúc 18:34

Ta có: \(\frac{xy}{z}+\frac{yz}{x}+\frac{zx}{y}=3\)

\(\Leftrightarrow x^2y^2+y^2z^2+z^2x^2=3xyz\ge0\)

\(\Rightarrow xyz\ge0\)(1)

Ta lại có: \(x^2y^2+y^2z^2+Z^2x^2\ge3xyz\sqrt[3]{xyz}\)

\(\Rightarrow3xyz\ge3xyz\sqrt[3]{xyz}\)

\(\Leftrightarrow xyz\le1\)(2)

Từ (1) và (2) ta được: \(0\le xyz\le1\)

Mà x, y, z khác 0 nên suy ra xyz = 1

\(\Rightarrow\)(x, y, z) = (1,1,1; -1,-1,1; -1,1,-1; 1,-1,-1)

Bình luận (0)

Các câu hỏi tương tự

Khoá học trên OLM của Đại học Sư phạm HN

Loading...

Khoá học trên OLM của Đại học Sư phạm HN